IMPACT OF THE CYCLE ON THE BANKRUPTCY OF ENTERPRISES IN POLAND IN THE YEARS 1990-2015 (Research Bulletins of the Faculty of Economic Sciences, 2018)
The article attempts to identify the bankruptcy of enterprises in Poland in the years 1990-2015 in the context of the business cycle. Permanent feature of the market economy, which is the occurrence of fluctuations affect the operations of enterprises. A review of previous studies on the relationship between bankruptcies and the economic cycle showed a negative correlation between the two phenomena. The article attempts to confirm the results of the research contained in the literature based on the years 1990-2015, so the twenty-six-year registration, the phenomenon of bankruptcy in Poland. The analysis was based on a simple linear regression model investigating the relationship between the number of bankruptcies and the dynamics of GDP and the dynamics of bankruptcy and the dynamics of GDP. The results are consistent with the results available in the literature and show a negative correlation. Their strength and direction determined by the pace of economic growth, which in the article is measured by GDP growth rate. Studies have shown large variability in the relationship between the phenomena studied in different periods. In the case depending on the number of bankruptcies of GDP growth strongest relationship occurs in the period 2005-2015 (r = -0.71). While examining the relationship dynamics of the bankruptcy of GDP growth, the strongest association occurred in the years 2000-2015 (r = 0.55).
Keywords: bankruptcy, bankruptcy proceedings, business cycle